Future costs in cost-effectiveness analysis: an empirical assessment - Kruse, Marie (Springer-Verlag, 2010)
AIM: The aim of this study was to assess the impact on the cost-effectiveness ratio of including measures of production and consumption following a health care or health promotion intervention that improves survival. DATA AND METHODS: We defined the net incremental consumption, or future costs, as the change in consumption minus change in production, while differentiating between health care and non-health care consumption. Based on 2005 register-based data for the entire Danish population, we estimated the average value of annual production and consumption for 1-year age groups. We computed the net consumption in the remaining expected lifetime and the net consumption per life year gained for different age groups. RESULTS: Age has a profound effect on the magnitude of net consumption. When including net incremental consumption in the cost-effectiveness ratio of a health care or health promotion intervention, the relative cost-effectiveness changed up to €21,000 across age groups. The largest difference in the cost-effectiveness ratio was observed among the 30-year-olds where costs were reduced significantly due to significant future net contributions to society. CONCLUSION: This paper contains cost figures for use in cost-effectiveness analyses, when the societal perspective is adopted and future consumption and production effects are taken into account. The net consumption varies considerably with age. Inclusion of net incremental consumption in the cost-effectiveness analysis will markedly affect the relative cost-effectiveness of interventions targeted at different age groups. Omitting future cost from cost-effectiveness analysis may bias the ranking of health care interventions and favour interventions aimed at older age groups. We used Danish data for this assessment, and our results will therefore not represent true figures for other countries. We do, however, believe that the overall impact of including net production value in CEA will be similar in other countries that have similar transfers of income from the younger age groups to older age groups as well as publicly financed social and health care services.